The development of therapeutic antibodies against oncogenic antigens - Seon, Ben (Henry Stewart Talks, 2020)
The development of naked and drug-conjugated antibodies against endoglin and CD75b, The results of recent clinical trials with both therapeutic antibodies, Advantages and challenges in the development of naked and drug-conjugated antibodies